Low Back Pain in Pregnancy - Barış Nacır; Aynur Karagöz; H. Rana Erdem (Archives of Rheumatology, 2009)
Pregnancy-related low back pain is a common problem during pregnancy. More than half of all pregnant women experience low back pain at some time during pregnancy. The pain can vary from a mild discomfort to being severe and disabling. In one-third of these women, pain is a severe problem compromising activities of daily living, work and sleep. The awareness of the possible impact of low back pain on the quality of life and the associated costs to society has increased medical attention over the last decade. Pain usually develops between the fifth and seventh month of pregnancy but may appear as early as the first trimester. Moreover, some women who experience back pain during pregnancy experience persistent back pain in the postpartum period or have an increased risk of back pain in subsequent pregnancies, and many women with chronic back pain link its onset to a pregnancy. Despite its high frequency, there are some ambiguities inherent in the terminology, diagnosis and classification. The etiology and pathogenesis are not yet clearly understood. The etiology of pain is probably related to a combination of mechanical, hormonal and vascular contributing factors. Low back pain in pregnancy is most commonly subdivided into lumbar pain and posterior pelvic pain. This subdivision is important in terms of both management and prognosis. Characteristic findings and treatment may differ between the two categories. Accurate assessment and effective treatment are important for managing the low back pain of pregnancy. The purpose of the present article was to provide a summary review of the performed studies on pregnancy-related low back pain. (Turk J Rheumatol 2009; 24: 39-45)